Qualitative investigation of skills and knowledge required for job readiness in newly graduated speech-language pathologists - Madhawi K. Altaib; Aseel Alkadhi; Ghada T.A. Najmaldeen; Lamya Aldukair (PLoS ONE, 2026)
This study explores the critical skills and knowledge that new speech and language pathologists (SLPs) must acquire to transition successfully into the workforce. While university programs aim to prepare students adequately, gaps remain in identifying the specific competencies essential for job readiness. This study employed a qualitative research approach, conducting focus group interviews with key stakeholders, including alumni, faculty, clinicians, and employers. Data were analyzed using thematic analysis. A total of 15 participants took part in five focus groups. The analysis identified four main themes: essential personal characteristics, exhibiting independence in managing work, foundational academic knowledge, and general clinical skills for SLPs . The findings emphasize the importance of traits such as a positive attitude, flexibility, and the ability to analyze situations and make informed decisions. Additionally, the study highlights the need to expand clinical training and integrate a more specialized curriculum. While some advanced topics require further exploration, they may be too complex for entry-level professionals without additional experience. Providing students with exposure to diverse clinical settings and work environments during training is also crucial. To better prepare newly graduated SLPs, university curricula must evolve to equip graduates with the necessary skills and knowledge for varied clinical settings and to meet the profession’s growing demands.